Leptospirosis Prevalence in Patients with Initial Diagnosis of Dengue - A. Dircio Montes Sergio; E. González Figueroa; Verdalet Guzmán María Saadia; Soler Huerta Elizabeth; Rivas Sánchez Beatriz; M. Altuzar Aguilar Víctor; J. Navarrete Espinosa (Journal of Tropical Medicine)
Objective. To determine the prevalence of leptospirosis in patients from Veracruz with initial diagnosis of dengue and its association with risk factors. Materials and Methods. Transversal study in patients who sought medical attention under the suspicion of dengue. Backgrounds were researched and blood samples were drawn to determine dengue (NS1, RT-PCR) and leptospirosis (IFI). Simple frequencies, central tendency and dispersion measures, and prevalence and trust intervals at 95% (IC95%) were obtained. Prevalence reasons (RP) and IC95% were obtained and a multivariate logistic model was applied, using SPSS V15. Results. 171 patients were included, 56% women (32±14 years) and 44% men (32±17 years). 48% of the cases (IC95% 40.5–55.4) was positive to dengue, with a cut point of 1 : 80, seroprevalence for leptospirosis was of 6% (IC95% 2.7–10); 12% (IC95% 7–16.5) was positive to both pathologies and 34% was negative to both tests. Although the largest number of isolations corresponded to serotype 2, the four dengue virus serotypes were identified. In the bivariate analysis, overcrowding RP = 1.33, (IC = 0.46–3.5), bathing in rivers (RP = 1.31, IC = 0.13–7.4), and walking barefoot (RP = 1.39, IC = 0.58–3.3) were the variables associated with leptospirosis, although the relation was not statistically significant. Conclusions. Leptospirosis prevalence in subjects under suspicion of dengue fever is high, as well as the coincidence of both infections. The results show the coexistence of overlapped outbreaks of several diseases sharing the side of transmission. It is necessary the intentional search of other pathologies, such as influenza, rickettsiosis, and brucella, among others.